THE EFFECT OF TRAINING AND MOTIVATION ON EMPLOYEE PERFORMANCE AT PT MUTIARA SAMUDERA PASAI - jalaludin, ahmad; ridwan, muhamad (BAIK Publishers, 2024)
The purpose of this study was to determine the effect of Training and Motivation on the Performance of PT. Mutiara Samudera Pasai employees. The method used in this study is a quantitative method, with analysis techniques of validity testing, reliability testing, classical assumption testing, simple and multiple linear regression testing. The sample used was 60 respondents, namely the entire population. The results of this study are: 1) There is a positive and significant influence of the Training (X1) and Motivation (X2) variables on Performance (Y) of 39.1%, obtained an R number (correlation coefficient) of 0.625. 2) There is a positive and significant influence of the Training (X1) and Motivation (X2) variables on Performance (Y) of 55.5%, obtained an R number (correlation coefficient) of 0.745. 3) There is a positive and significant influence of the variables Training (X1) and Motivation (X2) together on Performance (Y of 55.9%, obtained the R number (correlation coefficient) of 0.748. Suggestions in this study are expected that the Leader can increase Motivation so that employees can increase work productivity so that it can be more optimal, Management can improve the economic welfare of employees, Leaders are more careful in determining the type of training and training methods that have an impact on improving employee abilities